2016
DOI: 10.4143/crt.2015.029
|View full text |Cite
|
Sign up to set email alerts
|

Appendiceal Neuroendocrine, Goblet and Signet-Ring Cell Tumors: A Spectrum of Diseases with Different Patterns of Presentation and Outcome

Abstract: PurposeAppendiceal tumors are a heterogeneous group of diseases that include typical neuroendocrine tumors (TNET), goblet cell carcinoids (GCC), and atypical GCC. Atypical GCC are classified into signet-ring cell cancers (SRCC) and poorly differentiated appendiceal adenocarcinoids. The prognosis and management of these diseases is unclear because there are no prospective studies. The aim of this study is to assess the characteristics and outcome of appendiceal TNET, GCC, and SRCC patients.Materials and Methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
2
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(52 citation statements)
references
References 23 publications
1
46
2
3
Order By: Relevance
“…A German multicentre observational study reported aNENs displaying a 5-year OS of 83.1% vs 49.2% for non-carcinoid tumours (Benedix et al 2010). In addition, in a large series from the SEER database stratified by tumour size, the authors did not detect any significant difference in survival between patients who underwent RHC and those who underwent simple appendicectomy (Groth et al 2011), and this was confirmed by a more recent study of the same database (Shaib et al 2015), implying either that RHC does not affect the outcome or that RHC improves the outcome in patients with more severe disease. Another interesting point in this latter study is the fact that specific cancer survival rates could be calculated, as opposed to other databases collecting OS rates (Groth et al 2011) (Supplementary Table 8, see section on supplementary data given at the end of this article).…”
Section: Prognosissupporting
confidence: 66%
See 4 more Smart Citations
“…A German multicentre observational study reported aNENs displaying a 5-year OS of 83.1% vs 49.2% for non-carcinoid tumours (Benedix et al 2010). In addition, in a large series from the SEER database stratified by tumour size, the authors did not detect any significant difference in survival between patients who underwent RHC and those who underwent simple appendicectomy (Groth et al 2011), and this was confirmed by a more recent study of the same database (Shaib et al 2015), implying either that RHC does not affect the outcome or that RHC improves the outcome in patients with more severe disease. Another interesting point in this latter study is the fact that specific cancer survival rates could be calculated, as opposed to other databases collecting OS rates (Groth et al 2011) (Supplementary Table 8, see section on supplementary data given at the end of this article).…”
Section: Prognosissupporting
confidence: 66%
“…Furthermore, among 6824 black patients who underwent an appendicectomy, a similar prevalence (47.6%) of aNENs and benign non-endocrine cell tumours was reported (45.2%) (Coskun et al 2006). In a recent study from SEER, a higher proportion of white patients was observed in aNENs, but the difference was not statistically significant (Shaib et al 2015).…”
Section: Epidemiologymentioning
confidence: 99%
See 3 more Smart Citations